Effect of nutrition education using the podcast method on adolescent girls' knowledge and attitudes on anemia in Central Jakarta - Ra'afi Adlu; Adhila Fayasari (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Anemia is one of the nutritional problems in Indonesia and is the higher number in female adolescents. Anemia was caused by low nutrition intake, high intake of inhibitors, and low adherence to an iron tablet. Therefore, there should be new education methods to increase knowledge and attitudes toward anemia prevention during the COVID-19 pandemic. This study aims to determine the effect of education with audio podcast media about anemia on knowledge and attitudes. We conducted a quasi-experimental with a control group design on 68 female adolescents in 4 State Senior High School, Central Jakarta. We divided subjects into two groups, the podcast group as an intervention group and the flyer group as a control group. The intervention was conducted in four phases over two weeks period. Pretests and posttests were collected using an online questionnaire shared through a messaging platform. Posttests were conducted twice, after the intervention and two weeks after the intervention. We analyzed data using Wilcoxon and Mann-Whitney test with α= 0,05. The results showed there was an increase in knowledge (p= 0,000) and attitude (p= 0,036) scores in the audio podcast group, but for the flyer group, the significant increase was only in knowledge scores (p= 0,000). However, there was no difference increase in both methods (p>0,05). The podcast was significantly more effective in increasing knowledge (p= 0,007) than flyers, but not for attitudes (p= 0,389). Podcasts could be an alternative education method for adolescents. It shows effectiveness in increasing knowledge but not in attitudes, which needs more study.